Efficient biodegradation and upcycling of polyethylene terephthalate mediated by cell-factories - Liu, Fei; Wang, Tao; Liu, Xiao-huan; Xu, Na; Pan, Xing-li (Frontiers in Microbiology, 2025)
The pervasive accumulation of polyethylene terephthalate (PET) waste has emerged as a critical ecological crisis, which is mainly driven by its recalcitrance to natural degradation and widespread contamination of terrestrial and aquatic ecosystems. In response to this challenge, microbial-mediated PET biodegradation has garnered significant scientific attentions as a sustainable remediation strategy, harnessing the enzymatic cascades of specialized microorganisms to depolymerize PET into bio-assimilable monomers such as terephthalic acid (TPA) and ethylene glycol (EG). In this review, we summarize the extracellular process of PET biodegradation, including microbial attachment, colonization, and direct depolymerization, as well as the metabolic pathways of PET monomers. Strategies for developing PET-degrading chassis cells are also discussed, such as cell surface display, metabolic pathway optimization, and rational design of enzyme-PET interfaces. Microbial-enzyme consortia and molecular engineering of photosynthetic microorganisms also contribute to PET degradation. Although significant progress has been made, challenges remain in enzyme stability, metabolic bottlenecks, industrial scalability, and environmental adaptation. Overall, microbial and enzymatic strategies show great potentials in addressing PET pollution, and future interdisciplinary efforts are needed to overcome these challenges and achieve a sustainable circular plastic economy.